Application of ATR-FTIR for a rapid evaluation of storage life of fresh dwarf copperleaf via its moisture content. (September 2019) - Nesakumar, Noel; Baskar, Chanthini; Balaguru Rayappan, John Bosco; Alwarappan, Subbiah
Graphical abstract: Highlights: ATR-FTIR allowed rapid evaluation of freshness of dwarf copperleaf. Moisture changes occurring during storage were evaluated by FTIR. No sample pre-treatment is required. Abstract: Fresh dwarf copperleaf stored in a refrigerator at 0 °C lasts for 5 days and its shelf life depends on its moisture content. In this present work, the moisture changes in fresh dwarf copperleaf during refrigerated storage were evaluated employing Fourier transform infrared spectroscopy (FTIR). Subsequently, FTIR spectra were collected directly from the fresh dwarf copperleaf surface over a week employing attenuated total reflectance mode. The sample FTIR spectra were correlated with the freshness of dwarf copperleaf stored at 0 °C using principal component analysis. The sample FTIR spectra data were processed to estimate peak integrated data of FTIR spectrum ( ∫ ν ¯ i ν ¯ f T p d ν ¯ ) and transmittance peak ( T p ) using Gaussian function. T p and ∫ ν ¯ i ν ¯ f T p d ν ¯ were used as dependent variables for formulating biphasic dose response models by applying Levenberg-Marquardt algorithm for predicting the age of dwarf copperleaf. The performance of the proposed analytical method was good with an outstanding low relative prediction error ranging from 0.046% to 0.098% in the validation samples. The principal component analysis assisted ATR-FTIR spectroscopy could be considered as an alternative analytical tool for rapid and accurate evaluation of freshness of dwarf copperleaf during refrigerated storage conditions.